2018
DOI: 10.1681/asn.2017121273
|View full text |Cite
|
Sign up to set email alerts
|

Dialysis versus Medical Management at Different Ages and Levels of Kidney Function in Veterans with Advanced CKD

Abstract: Appropriate patient selection and optimal timing of dialysis initiation among older adults with advanced CKD are uncertain. We determined the association between dialysis versus medical management and survival at different ages and levels of kidney function. We assembled a nationally representative 20% sample of United States veterans with eGFR<30 ml/min per 1.73 m between 2005 and 2010 (=73,349), with follow-up through 2012. We used an extended Cox model to determine associations among the time-varying exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…Therefore, as the authors of the REIN score also point out, the transportability of these models to advanced CKD patients who have yet to decide on a treatment strategy is unsure [ 28 ]. Multiple studies have compared survival in patients treated with dialysis and CC from an aetiological perspective and demonstrated a limited survival benefit of dialysis in patients with higher age and more comorbidities [ 8 , 14 , 29 ]. However, no mortality prediction model for patients on CC has previously been developed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, as the authors of the REIN score also point out, the transportability of these models to advanced CKD patients who have yet to decide on a treatment strategy is unsure [ 28 ]. Multiple studies have compared survival in patients treated with dialysis and CC from an aetiological perspective and demonstrated a limited survival benefit of dialysis in patients with higher age and more comorbidities [ 8 , 14 , 29 ]. However, no mortality prediction model for patients on CC has previously been developed.…”
Section: Discussionmentioning
confidence: 99%
“…In order to foster shared decision-making and personalized treatment, patients should be provided with accurate information on their prognosis for each treatment strategy [ 5 , 8 ]. There is a large range in survival time of patients on both dialysis and CC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bowling et al [89] conducted a cohort study in 357,632 CKD patients aged � 70 years and showed that median survival time decreased with progression in either age or CKD stage; patients aged � 85 years had the lowest survival ranging from 1.9 (CKD stage 4) to 3.2 years (CKD stage 2). Tamura et al [90] estimated survival among 73,349 older ESRD patients (� 60 years) initiating dialysis at different kidney function levels. The study revealed that median survival was diminished upon initiating dialysis at higher GFRs as well as with older age.…”
Section: Le Among Ckd Patientsmentioning
confidence: 99%
“…When taking into account a dropout rate of 10%, 99 patients on CC and 394 on dialysis are needed, a total of 493 patients. Based on a study from the United States, we expected one third of patients to progress from stage one to two within 3 years, so a cohort of 1500 patients will be needed [ 49 ].…”
Section: Methodsmentioning
confidence: 99%